2014
DOI: 10.1097/qad.0000000000000231
|View full text |Cite
|
Sign up to set email alerts
|

Safety of efavirenz in the first trimester of pregnancy

Abstract: This updated analysis found no evidence of an increased risk of overall or central nervous system congenital anomalies associated with first-trimester exposure to efavirenz, similar to previous systematic reviews. This review contributed to the evidence base for the revised 2013 WHO guidelines on antiretroviral therapy, which recommend that efavirenz can be included as part of first-line therapy in adults regardless of sex, and that it can be used throughout pregnancy, including during the first trimester. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(34 citation statements)
references
References 30 publications
4
27
1
2
Order By: Relevance
“…The effect of maternal HIV and alcohol use on gestational may be attenuated by ARTs with similar findings from several recent meta-analyses and systematic reviews showing good maternal and infant outcomes for HIV-infected mothers on ARTs [47, 48]. While such findings are positive, they do not negate the potentially harmful effects of HIV and alcohol on long-term developmental outcomes of children, which need to be explored further.…”
Section: Discussionsupporting
confidence: 52%
“…The effect of maternal HIV and alcohol use on gestational may be attenuated by ARTs with similar findings from several recent meta-analyses and systematic reviews showing good maternal and infant outcomes for HIV-infected mothers on ARTs [47, 48]. While such findings are positive, they do not negate the potentially harmful effects of HIV and alcohol on long-term developmental outcomes of children, which need to be explored further.…”
Section: Discussionsupporting
confidence: 52%
“…Several meta analyses of chemical exposures during pregnancy include but are not limited to: pollution 69 , secondhand smoke 70 , efavirenz 71 , polychlorinated biphenyls and dichlorodiphenyldichloroethylene 72 , domestic violence 73 , antidepressant use 74,75 , shift work 76 , statins 77 , and maternal obesity 78 . Many of the exposures listed were correlated with preterm birth, altered size and weight of the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Previous teratogenicity concerns arose from primate studies, and there are no available direct data from human studies. However, meta-analyses of the literature have shown that first-trimester EFZ exposure is not associated with higher risk to teratogenicity [13]. Possibly following the USA’s HHS panel updates, Brazil’s Ministry of Health recently issued a similar update to its guidelines.…”
Section: Antiretroviral Drug Regimens For Hiv-1 Mother To Child Trmentioning
confidence: 99%